2013
DOI: 10.2337/dc12-0453
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Imeglimin as Add-on Therapy in Patients With Type 2 Diabetes Inadequately Controlled With Metformin Monotherapy

Abstract: OBJECTIVEA 12-week study assessed the efficacy and safety of a new oral antidiabetic agent, imeglimin, as add-on therapy in type 2 diabetes patients inadequately controlled with metformin alone.RESEARCH DESIGN AND METHODSA total of 156 patients were randomized 1:1 to receive imeglimin (1,500 mg twice a day) or placebo added to a stable dose of metformin (1,500–2,000 mg/day). Change in A1C from baseline was the primary efficacy outcome; secondary outcomes included fasting plasma glucose (FPG) and proinsulin/ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 8 publications
4
85
0
1
Order By: Relevance
“…IMEG, imeglimin; JO 2 , mitochondrial oxygen consumption rate; prot mito, protein mitochondria; Rot, rotenone; Succ, succinate. demonstrated that in addition to its efficacy as monotherapy, imeglimin could complement the actions of metformin or sitagliptin by significantly improving HbA 1c and fasting plasma glucose in type 2 diabetic patients (3,4). In this study, we investigated the mechanism of action of imeglimin on glucose homeostasis in HFHSD-induced diabetic mice and demonstrated the efficacy of imeglimin on glucose homeostasis after 6 weeks of treatment in this model.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…IMEG, imeglimin; JO 2 , mitochondrial oxygen consumption rate; prot mito, protein mitochondria; Rot, rotenone; Succ, succinate. demonstrated that in addition to its efficacy as monotherapy, imeglimin could complement the actions of metformin or sitagliptin by significantly improving HbA 1c and fasting plasma glucose in type 2 diabetic patients (3,4). In this study, we investigated the mechanism of action of imeglimin on glucose homeostasis in HFHSD-induced diabetic mice and demonstrated the efficacy of imeglimin on glucose homeostasis after 6 weeks of treatment in this model.…”
Section: Discussionmentioning
confidence: 90%
“…Imeglimin is the first in a new tetrahydrotriazine-containing class of oral glucose-lowering agents-the glimins-and is currently in phase 2b clinical development (U.S./European Union EudraCT 2012-004045-33). Several clinical trials have shown imeglimin to be well tolerated and exhibit benefits on HbA 1c as monotherapy and add-on therapy (3)(4)(5). Imeglimin acts on the liver, muscle, and the pancreas (6), three key organs involved in the pathophysiology of type 2 diabetes through suspected mechanisms targeting the mitochondria and reduced oxidative stress.…”
mentioning
confidence: 99%
“…The triazine derivative, imeglimin, improved glycemic control in clinical trials . Preclinical studies indicated enhanced glucose‐induced insulin secretion, reduced hepatic gluconeogenesis, and improved glucose disposal.…”
Section: Future Diabetes Therapiesmentioning
confidence: 99%
“…The triazine derivative, imeglimin, improved glycemic control in clinical trials. 33 Preclinical studies indicated enhanced glucoseinduced insulin secretion, reduced hepatic gluconeogenesis, and improved glucose disposal. Many other compounds have improved beta cell function in vitro, including selective phosphodiesterase inhibitors and succinate esters, but targeting these specifically to the beta cells in vivo has been insurmountable.…”
Section: Promoting Beta Cell Functionmentioning
confidence: 99%
“…The efficacy and safety profile of imeglimin was similar in chronic kidney disease patients when compared with individuals with normal renal function (Poxel Pharma, ). Additionally, unpublished data by Poxel indicates that imeglimin did not alter metformin concentrations in health subjects, implying the lack of imeglimin‐metformin drug–drug interactions (Fouqueray et al, ).…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%